SOLUTE AND PARTICULATE ORGANIC MATERIAL OF THE SAKHALIN ISLAND SHELF - Nemirovskaya I.A.; Lyutsarev S.V.; Shanin S.S. (My University, 1997)
The solute and particulate contents of organic materials, lipids, and aliphatic and polycyclic aromatic hydrocarbons (PAHs) in surface and near-bottom waters are measured in the Bay of Sakhalin in the areas of the Astrakhan geologic structure (Area A), and Lozin (Area B), Bautin (Area C), and Arkutun-Dagi (Area D) oil and gas deposits located in the NE Sakhalin shelf. In the east region of the shelf, the parameters in question average 1.6-2.3 mg/1 for solute organic material (SOM), 16.5-23.8 μg/l for particulate organic material (POM), 18.3-22.8 μg/l for solute hydrocarbons (HCs), 8.0-31.2 μg/l for particulate hydrocarbons (HCp), 4.4-12.7 ng/l for PAHS, and 47.5-96.7 ng/l for PAHp. These ranges are close to the respective concentrations determined previously in the coastal seawaters and may be taken as the background level ranges. In the Bay of Sakhalin, all types of organic compounds show elevated levels, occasionally exceeding the maximum permissible level (50 μg/l) for petroleum hydrocarbons. The alkane and PAH spectra suggest that the elevated concentrations are natural and caused by the discharge of the Amur river and the inflow from bottom sediments.